Analysis of Pharmaceutical Logistics Control Management. Qualitative Study at the Pharmaceutical Installation of Hajj General Hospital Medan in 2021 - Afif Husain Faizar; Rahmat Alyakin Dachi; Dewi R Bancin; Donal Nababan; Asima Sirait (Jurnal Info Sains : Informatika dan Sains, 2023)
Medicines as a hospital's current assets are very important for patient survival because 90% of health service interventions in hospitals prioritize medicines. There is a shortage of medicines, running out of medicine stocks or medicines piling up, which has medical and economic impacts. Things like this require efficient and effective drug management efforts. At RSU Haji, the supply of medicines in the Pharmacy Installation is a variable that has a number of dissatisfaction in management and the medicines provided are still not effective enough, there are problems with input components such as human resources, procurement, supervision and output (stock out, expired medicines, stock taking) which is not yet effective. The purpose of this study is the Analysis of Management of Pharmaceutical Logistics Control in a Qualitative Study at the Pharmacy Installation of the Medan Haji General Hospital in 2021. The type of research is qualitative with a phenomenological study design. Respondent are a Head of Pharmacy Installation, Coordinator of Pharmacy Services, Pharmacy Installation Pharmacist Assistant, Inpatient Pharmacist Assistant, Outpatient Pharmacist Assistant, Pharmacy Warehouse Coordinator for Pharmacy Warehouse Staff, Financial Management of Hajj Hospital in Medan City. The data used includes primary data and secondary data. Data collection by interviews, data management and data analysis using data reduction, data presentation and drawing conclusions. The results of the study show that in the pharmaceutical logistics of the Hajj Hospital there are still obstacles, namely the lack of human resources in the pharmacy technician section so that the work is carried out by double staff and the need to improve the budget and review of infrastructure facilities in the pharmaceutical logistics management aspect of the Hajj Hospital Medan. It is hoped that the RSU Hajj will add human resources to improve the quality of drug logistics management so that management will be even better.